Case report: Whole-exome sequencing for a hereditary elliptocytosis case with an unexpectedly low HbA1c - Pang, Lu; Zeng, Ziyi; Ding, Yadi; Huang, Haiming; Li, Haixia (Frontiers in Medicine, 2023)
Objectives Hereditary elliptocytosis is a group of erythroid hereditary diseases characterized by elliptically shaped erythrocytes in peripheral blood. It is mainly inherited through autosomal dominant inheritance. This study aimed to conduct a genetic etiology analysis in a case with a clinical diagnosis of hereditary elliptocytosis and an unexpectedly low HbA1c. Methods Whole-exome sequencing was performed to find the possible pathogenic mutations. At the same time, bioinformatics software was used to predict the mutation function. Sanger sequencing was performed to verify the suspected pathogenic mutations. Results Whole-exome sequencing results showed that the proband with mild anemia had a heterozygous c.2303G>A (p.G768D) missense mutation in the 13th exon of the SPTB gene. The Sanger sequencing confirmed this heterozygous mutation. This mutation was extremely rare in the population, and multiple software’s predictions were harmful. Conservative analysis revealed that this site was highly conserved in various species. Conclusion The c.2303G>A mutation of the SPTB gene is the suspected cause of hereditary elliptocytosis in the patient. Our data show that microscopic examination of red blood cells on blood smears is an important means of diagnosing hereditary elliptocytosis. Whole-exome sequencing is an effective tool to determine the genetic etiology of erythrocyte membrane diseases, which can promote accurate diagnosis and genetic counseling.